(untitled) (Journal of Governance and Development (JGD), 2025)
Digital transformation in government is reshaping the way public institutions deliver services, manage data, and interact with citizens. In Indonesia, the push toward an integrated electronic government system has been hindered by fragmented institutional behaviors and limited interoperability across ministries. This study addresses the gap by analyzing how organizational structures and interministerial dynamics affect system integration within Indonesia’s national digital governance framework. This research employs a mixed-methods approach, combining qualitative and quantitative strategies. Qualitative data were collected through in-depth interviews and document analysis to explore institutional behaviors and coordination mechanisms. Quantitatively, interoperability maturity was measured across four dimensions: technical, semantic, organizational, and legal, using network analysis mapping to visualize interministerial relationships and data exchange structures. The study focuses on three key ministries: The Ministry of Home Affairs, the Ministry of Bureaucratic Reform, and the Ministry of Communication and Information Technology. Findings reveal asymmetries in the maturity of interoperability among ministries. While legal and organizational dimensions show moderate alignment, semantic and technical interoperability remain underdeveloped. The Ministry of Communication and Information leads in technical and semantic areas, whereas the Ministry of Home Affairs demonstrates weaker integration. These disparities reflect autopoietic tendencies where ministries operate through self-referential logic, hindering systemic coordination. Interview data support the presence of loose coupling, symbolic compliance, and institutional path dependency that obstruct integration efforts. The research integrates systems theory and institutional theory to argue that digital transformation requires structural coupling between autonomous government systems. Without shared standards, semantic alignment, and cross-sectoral governance mechanisms, integration efforts risk being superficial. The study proposes the establishment of a National Interoperability Council to facilitate coordinated digital governance, mediate inter-agency challenges, and foster accountability. These findings offer both theoretical contributions and policy recommendations for building a more responsive and integrated digital government in Indonesia.